2017
DOI: 10.4236/gep.2017.58010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Shallow Groundwater Quality in Four Districts with Different Characteristics in Urban Area (Douala, Cameroon)

Abstract: This study examines groundwater samples from four areas under different conditions. Variations amongst the areas are due to the distinct topography, demographics, and socio-economic activities. A qualification of the groundwater using the following parameters; pH, electric conductivity and nitrate analysis yielded results depicting the deplorable state of the unconfined aquifer; which is even worst in the densely populated and low-lying areas. These unfavorable conditions are present in the older districts (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The action of microorganisms, the proximity of latrines and other anthropogenic factors may also influence the pH of water [36]. The pH levels corroborated with values documented in Melong by Mufur et al [13] and in Bamenda by Akoanung et al [4] but were very low compared to those obtained by Ketchemen-Tandia et al [37] in Douala (Littoral Cameroon) and Mukhopadhyay et al [38] in West Bengal. Electrical Conductivity values for all the water samples ranged from 0.05 to 0.25 during the rainy period whereas during the dry period it varied between 0.08 and 0.38 µS/cm.…”
Section: Physical Propertiessupporting
confidence: 80%
“…The action of microorganisms, the proximity of latrines and other anthropogenic factors may also influence the pH of water [36]. The pH levels corroborated with values documented in Melong by Mufur et al [13] and in Bamenda by Akoanung et al [4] but were very low compared to those obtained by Ketchemen-Tandia et al [37] in Douala (Littoral Cameroon) and Mukhopadhyay et al [38] in West Bengal. Electrical Conductivity values for all the water samples ranged from 0.05 to 0.25 during the rainy period whereas during the dry period it varied between 0.08 and 0.38 µS/cm.…”
Section: Physical Propertiessupporting
confidence: 80%
“…Studies performed in the northwest of China reported high nitrate concentrations representing health risk concerns for the population [38] due to anthropogenic activities, especially fertilizers used in agriculture [39]. N-bearing and P-bearing fertilizers can cause the oxidation of geogenic Cr, which results in elevated Cr 6+ [19]. Wei et al [34] also reported that nitrate pollution was a major environmental geological problem in the groundwater in part of China.…”
Section: Introductionmentioning
confidence: 99%
“…There is a critical increase in freshwater demand correlated with the rapid growth of the population all over the world [14] and intensive agriculture activities [15,16]. The increment of the population also leads to the expansion of cities and municipal waste that affect the groundwater quality through organic and inorganic contaminants [17][18][19][20]. Furthermore, industrialization is one of the most significant factors affecting groundwater quality through the effluents released into the nature [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, much urban growth occurs in or around already overcrowded urban shantytowns, periurban areas and informal settlements [24]. Thus, in these low-income neighbourhoods, groundwater contamination is attributed to surface water percolation, septic tanks, cesspools, and latrines using animal manure stored in landfills or applied to agricultural land as fertilizer [15,30,33,34,42,53].…”
Section: Introductionmentioning
confidence: 99%